Genomic and transcriptomic heterogeneity in metaplastic carcinomas of the breast. (December 2017) - Piscuoglio, Salvatore; Ng, Charlotte; Geyer, Felipe; Burke, Kathleen; Cowell, Catherine; Martelotto, Luciano; Natrajan, Rachael; Popova, Tatiana; Maher, Christopher; Lim, Raymond; Bruijn, Ino; Mariani, Odette; et al.
Abstract Metaplastic breast cancer (MBC) is a rare special histologic type of triple-negative breast cancer, characterized by the presence of neoplastic cells showing differentiation towards squamous epithelium and/or mesenchymal elements. Here we sought to define whether histologically distinct subgroups of MBCs would be underpinned by distinct genomic and/or transcriptomic alterations. Microarray-based copy number profiling identified limited but significant differences between the distinct MBC subtypes studied here, despite the limited sample size (n = 17). In particular, we found that, compared to MBCs with chondroid or squamous cell metaplasia, MBCs with spindle cell differentiation less frequently harbored gain of 7q11.22-23 encompassingCLDN3 andCLDN4, consistent with their lower expression of claudins and their association with the claudin-low molecular classification. Microarray-based and RNA-sequencing-based gene expression profiling revealed that MBCs with spindle cell differentiation differ from MBCs with chondroid or squamous cell metaplasia on the expression of epithelial-to-mesenchymal transition-related genes, including down-regulation ofCDH1 andEPCAM . In addition, RNA-sequencing revealed that the histologic patterns observed in MBCs are unlikely to be underpinned by a highly recurrent expressed fusion gene or a pathognomonic expressed mutation in cancer genes. Loss of PTEN expression or mutations affectingPIK3CA orTSC2 observed in 8/17 MBCs support the contention that PI3K pathway activation plays a role in the development of MBCs. Our data demonstrate that despite harboring largely similar patterns of gene copy number alterations, MBCs with spindle cell, chondroid and squamous differentiation are distinct at the transcriptomic level but are unlikely to be defined by specific pathognomonic genetic alterations. Genetics: no common genetic basis found for metaplastic breast carcinoma Recurrent somatic genetic alterations in any known cancer gene are unlikely to underpin metaplastic breast carcinoma (MBC), a rare breast cancer type. Jorge Reis-Filho from Memorial Sloan Kettering Cancer Center in New York, NY, USA, and colleagues performed complete genomic work-ups of 17 MBCs, an invasive form of breast cancer characterized by tumor cells displaying differentiation towards other cell types. Albeit limited, important differences in gene copy number and gene expression profiles between different subtypes of MBC were observed. These tumors were incredibly variable from patient to patient, and there were no defining genomic features that could demarcate the disease on a genetic level from other forms of triple-negative breast cancer. The authors suggest that further studies are needed to explain the basis of the diversity seen in MBCs.